Taxation, inequality and the allocation of talent - Malin L. Bergman (Stockholm School of Economics, The Economic Research Institute (EFI), 2003)
This paper examines the implications of income redistribution on human capital accumulation and income inequality, presenting a model where human capital investment is indivisible and agents differ in economic opportunity as well as intellectual ability. It is shown that the impact of redistribution is ambiguous on the income distribution as well as on human capital accumulation. In particular, while redistributive policy is likely to be successful both in terms of efficiency and equity in low-tax societies, it may be highly detrimental in both respects if the rate of redistribution is already moderate or high.
Keywords: H31; J24; 330; human capital; talent; efficiency; equity; redistributive taxation